Gubernatorial candidates in polarizing times: examining gubernatorial discourse through political interviews - Ingmire, Brock (Kansas State University, 2015)
The rise of partisan political news over the past two decades has influenced how political candidates discursively construct their image. While there is an extensive literature devote to presidential discourse, little is known about what gubernatorial discourse looks like and how they construct their image. This study examines how gubernatorial candidates discursively construct their image in a hyperpolarized electoral environment. An extensive content analysis of gubernatorial political interviews (n = 94), and specifically the utterances arising from those interviews (n = 1,524), was conducted. Findings show that gubernatorial candidates discursively construct their own image as a savior to the state, while creating their opponent’s and the DC elite’s image as a villain. Additionally, gubernatorial candidates do not adhere to the image bound by their party, and construct an image that is unique to their environment. Consequently, the environment that a gubernatorial candidate is situated influences how they communicate and construct their image and their opponent’s image. By examining gubernatorial discourse through political interviews, this study offers theoretical implications into understanding the influence of polarization, issue ownership, and tone in gubernatorial discourse. Practical implications examine the role of media outlets in gubernatorial discourse. This study contributes to scholarly understanding of gubernatorial discourse in a changing and polarizing political environment.
Keywords: Gubernatorial discourse; Political interview; Election; Polarization; Issue ownership; Communication (0459)